2020
DOI: 10.1039/d0lc00906g
|View full text |Cite
|
Sign up to set email alerts
|

Trapping and control of bubbles in various microfluidic applications

Abstract: Active and passive techniques for bubble trapping and control in various microfluidic applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 121 publications
0
20
0
Order By: Relevance
“…[51] We obtain a maximum NB generation frequency of 10 5 s −1 with a gas pressure of 15 psi and a liquid flow rate of 3 mL hr −1 , which leads to a final bubble concentration of ≈10 8 mL −1 . Further scale-up of the production throughput is possible by optimizing the microfluidic design, employing higher flow rates and gas pressures, parallelizing flow-focusing orifices, [52] and concentrating MBs with microcavity trapping structures, [53] followed by subsequent shrinkage to NBs. Importantly, this method generates NBs without significant changes to typical microfluidic bubble preparation methods, and without needing to improve the manufacturing resolution of microfluidic devices.…”
Section: Shrinking Mbs To Nbsmentioning
confidence: 99%
“…[51] We obtain a maximum NB generation frequency of 10 5 s −1 with a gas pressure of 15 psi and a liquid flow rate of 3 mL hr −1 , which leads to a final bubble concentration of ≈10 8 mL −1 . Further scale-up of the production throughput is possible by optimizing the microfluidic design, employing higher flow rates and gas pressures, parallelizing flow-focusing orifices, [52] and concentrating MBs with microcavity trapping structures, [53] followed by subsequent shrinkage to NBs. Importantly, this method generates NBs without significant changes to typical microfluidic bubble preparation methods, and without needing to improve the manufacturing resolution of microfluidic devices.…”
Section: Shrinking Mbs To Nbsmentioning
confidence: 99%
“…Traditional trapping techniques are another form of fluid manipulation and include electrical, optical, thermal, magnetic, and acoustic. [ 105 ] Figure 7F shows a device using an automated fluid flow for the fine manipulation of micro‐ and nanoscale particles and particle trapping. [ 106 ] This flow control device consists of a fluidic layer (red) and a control layer (black).…”
Section: Application In Biomedical Engineering and Healthcarementioning
confidence: 99%
“…As an emerging tool in fluids and cell manipulation, acoustic bubbles in microfluidics show the possibility to address the challenges above. 16,17 In low-frequency acoustic fields, bubbles can be remotely excited to act as pumps, 18,19 mixers, 20,21 switches, 22 sorters 14,23 and transporters 24 in various lab-on-a-chip (LOC) applications. Acoustic bubbles can generate secondary radiation force (SRF) on cells at a specific frequency range, which could be harnessed to trap and rotate cells on the bubble surface when the radiation force exceeds the external drag forces.…”
Section: Introductionmentioning
confidence: 99%
“…In microfluidic devices, the location of the bubbles can be precisely controlled by both active and passive methods, making it possible to trap cells and particles in desired locations. 17 Additionally, it is shown that the acoustic bubble is biocompatible in manipulating tumor cells and microorganisms, which could help maintain cell viability. 26,27 These above advantages make the acoustic bubble a promising candidate for CTC-processing.…”
Section: Introductionmentioning
confidence: 99%